Lumbar Puncture in a Teaching Hospital: Indications, Findings, and Complications over Five Years with Adult Patients - Ba-Abbad, Shada; Dahbour , Aladdin; Akileh , Mays; Ghaith, Basel; Dahbour , Said (Jordan Medical Journal, 2022)
Background: Lumbar puncture (LP) is a bedside procedure used to investigate diseases of the central and peripheral nervous systems. We report the experience of a major teaching hospital in this procedure over a 5-year period. Methods: Medical records were reviewed of patients aged ≥ 13 years who underwent LP in the years 2014¬–2018. Age, gender, technique, indications, findings, complications, and final diagnosis were analyzed. Results: 195 patients, of whom 133 (68.2%) were females (aged 40.0 ±15.7) were studied. Opening pressure was measured in 104 (53.3%) patients (86, 82.7% females) showing a mean of 31.2±12.1cm, and closing pressure was measured in 54 (27.7%) patients with a mean of 16.5±5.7cm. Leukocyte and erythrocyte counts, and glucose and protein levels were measured in most patients (99.0%, 98.5%, 96.9%, and 96.9%, respectively). Bacterial culture and gram stain were performed in 28 (14.4%) and six (3.1%) patients, respectively. Cytology and oligoclonal bands were studied in 16 (8%) and 28 (14.4%) patients, respectively. Headache, peripheral neuropathy, and papilledema were the main indications found in 69 (35.4%), 41 (21.0%), and 26 (13.3%) patients, respectively. The most common final diagnoses were idiopathic intracranial hypertension, central nervous system inflammatory diseases, peripheral neuropathy, and meningoencephalitis in 68 (34.9%), 27 (13.3%), 20 (10.3%) and 16 (8.7%) patients, respectively. No major complications were recorded. Conclusions: LP is a common bedside procedure and the most common indications were intracranial pressure and inflammatory neurological disorders. It is a quite safe and useful procedure.